COVID-19 and emerging environmental trends a way forward - Dutta, Joystu; Goswami, Srijan; Mitra, Abhijit (CRC Press, Taylor & Francis Group, 2021)
This book revolves around the COVID-19 and its influence on all biotic and abiotic components on earth, with focus on the regulatory role of air quality during this pandemic, municipal solid waste management and COVID-19, how herd immunity influences COVID-19 and so on. With amalgamation of emerging environmental issues and the direct and indirect influences of COVID-19 on all these issues, it explains how pandemics change our thought and reset our priorities for action on a global scale. The book also explains control and mitigation of COVID-19 and cutting-edge research on COVID-19 with an empirical review on scientific efforts. Aimed at graduate students, researchers in environmental and medical sciences, health and safety, and ecology, this title Discusses direct and indirect influences of COVID-19 on related environmental issues Includes a multi-perspective and multi-disciplinary approach to the analysis and discussion of various global issues supported by case studies Analyses global environmental problems across multiple levels of abstraction Reviews epigenetic to ecosystem-level analysis and exploration of environmental pollution and its role in sparking public health crises Underlines environmentalists' efforts to make people aware of issues of globally emerging scenarios"--